Perceptions and knowledge of medical students about HIV and AIDS - Cunha, Alyne Condurú dos Santos; Ribeiro, Murilo Eduardo Soares; Silva, Adriana Veiga da Conceição; Andrade, Letícia da Cunha; Malcher, Claudia Marques Santa Rosa; Pessoa, Monaliza dos Santos (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and Objectives: The degree of information is not restricted to informative and opportunity issues of knowledge, but also to the development of a conscious individual perception for the adoption of preventive practices. This study aimed to assess the perception and knowledge of medical students about HIV and AIDS. Methods: This is a cross-sectional, observational, and unicentric study, through the application of a structured questionnaire and two referring to the attitude towards HIV and the individual risk perception and knowledge on modes of transmission. Student’s and Pearson’s Chi-Square Tests were applied, with p